Augmented reality exposure treatments in anxiety and related disorders: A systematic review - Jorge Grimaldos; Sara Fernández-Buendía; Juana Bretón-López; Clara Miguel; Pim Cuijpers; Soledad Quero (Internet Interventions)
Numerous controlled trials have been conducted to evaluate the effectiveness of virtual reality (VR) in exposure treatment for different anxiety disorders. Additionally, several meta-analyses focusing on VR studies are now available. In contrast, the number of studies that focus exclusively on augmented reality (AR) is smaller, and, to the best of our knowledge, there are currently no systematic reviews or meta-analyses available on this topic. The aim of this work is to conduct a systematic review focused exclusively on studies that evaluate the effectiveness of AR in the exposure treatment of anxiety and related disorders. Systematic searches were carried out in PubMed, PsycINFO, and Embase in January 2025. After the screening of 622 references, thirteen studies were included, twelve of which focused on phobic disorders. Overall, the results of the included studies are promising for the use of AR for conducting the exposure treatment, especially for specific phobias. Furthermore, AR achieved high satisfaction rates and was perceived as less aversive than in vivo exposure based on participants' experiences. However, some limitations should be noted regarding the state of this field of research, especially regarding the small number of included articles and the lack of sufficient RCTs to draw firm conclusions about the efficacy of AR, highlighting the need for further research in this field.